Diagnostic Performance of Theranostic Radionuclides Used in Transarterial Radioembolization for Liver Cancer - Li, Rou; Li, Danni; Jia, Guorong; Li, Xiao; Sun, Gaofeng; Zuo, Changjing (Frontiers in Oncology, 2021)
Primary liver tumor with hepatocellular carcinoma accounting for 75–80% of all such tumors, is one of the global leading causes of cancer-related death, especially in cirrhotic patients. Liver tumors are highly hypervascularized via the hepatic artery, while normal liver tissues are mainly supplied by the portal vein; consequently, intra-arterially delivered treatment, which includes transarterial chemoembolization (TACE) and transarterial radioembolization (TARE), is deemed as a palliative treatment. With the development of nuclear technology and radiochemistry, TARE has become an alternative for patients with hepatic cancer, especially for patients who failed other therapies, or for patients who need tumor downstaging treatment. In practice, some radionuclides have suitable physicochemical characteristics to act as radioactive embolism agents. Among them, 90Y emits β rays only and is suitable for bremsstrahlung single photon emission computed tomography (BS SPECT) and positron emission tomography (PET); meanwhile, some others, such as 131I, 153Sm, 166Ho, 177Lu, 186Re and 188Re, emit both β and γ rays, enabling embolism beads to play a role in both therapy and single photon emission computed tomography (SPECT) imaging. During TARE, concomitant imaging provide additive diagnostic information and help to guide the course of liver cancer treatment. Therefore, we review the theranostic radionuclides that have been used or could potentially be used in TARE for liver cancer and focus on the clinical benefits of diagnostic applications, including real-time monitoring of embolism beads, evaluating irradiation dose, predicting therapy effects, and corresponding adjustments to TARE.